2017
DOI: 10.1099/jgv.0.000702
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant fowlpox virus vector-based vaccines: expression kinetics, dissemination and safety profile following intranasal delivery

Abstract: We have previously established that mucosal uptake of recombinant fowlpox virus (rFPV) vaccines is far superior to other vector-based vaccines. Specifically, intranasal priming with rFPV vaccines can recruit unique antigen-presenting cells, which induce excellent mucosal and systemic HIV-specific CD8+ T-cell immunity. In this study, we have for the first time investigated the in vivo dissemination, safety and expression kinetics of rFPV post intranasal delivery using recombinant viruses expressing green fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…In summary, systemic rFWPV immunization probably elicited a faster innate immune response than systemic rAd immunization. Our observations are supported by a report that transgenes are already expressed in vivo 6 h after rFWPV vaccination (65). Moreover, similar to our results, other studies showed that Ad5 in general evokes relatively low innate immune responses compared to other adenoviruses (66,67), probably because Ad5 migrates into the nucleus relatively quickly (68).…”
Section: Discussionsupporting
confidence: 92%
“…In summary, systemic rFWPV immunization probably elicited a faster innate immune response than systemic rAd immunization. Our observations are supported by a report that transgenes are already expressed in vivo 6 h after rFWPV vaccination (65). Moreover, similar to our results, other studies showed that Ad5 in general evokes relatively low innate immune responses compared to other adenoviruses (66,67), probably because Ad5 migrates into the nucleus relatively quickly (68).…”
Section: Discussionsupporting
confidence: 92%
“…booster with recombinant vaccinia virus (rVV) or rMVA expressing HIV antigens, induced sustained mucosal and systemic HIV-specific CD8 + T cell immunity 27,38 . rFPV was a useful intranasal priming delivery vector 27,37,39 and does not cross the olfactory receptor neuron pathway 40 , similar to what has been reported with rMVA 23 . Our studies also led to the discovery that IL-13 plays a crucial role in modulating T cell avidity in a route dependent manner, where mucosal vaccination induced high avidity T cells with improved efficacy by lowering innate lymphoid cells type 2-driven IL-13 expression at the vaccination site 41 and T cell driven IL-13 at the adaptive immune level 28,42,43 .…”
Section: Introductionsupporting
confidence: 75%
“…The mismatch of the antigenicity between the "old" vaccines and the currently circulating pathogens has frankly compromised the vaccine protective efficacy. To overcome the problem associated with this mismatch, researchers have developed viral vectors such as turkey herpesvirus, NDV, and fowlpox virus (Bublot et al, 2006;Esaki et al, 2013;Townsend et al, 2017;Kim and Samal, 2018) to deliver antigens that can match with the variants of currently circulating pathogens. Among these vectors, NDV has been demonstrated to be one of the most promising candidates for developing multivalent poultry vaccines (Dimitrov et al, 2017;Kim and Samal, 2018).…”
Section: Discussionmentioning
confidence: 99%